2013
DOI: 10.15361/2175-0106.2013v29n3p175-182
|View full text |Cite
|
Sign up to set email alerts
|

EVALUATION OF BABASSU MESOCARP MEAL IN FEED FOR BROILER CHICKENS / Avaliação do mesocarpo de Babaçu (Orbignya ssp) na alimentação de frangos de corte.

Abstract: SUMMARYThis study evaluates nutritional value and use of babassu mesocarp supplementation in the feeding of broilers. Initially, the chemical composition was determined in order to characterize the ingredient. Then two tests were conducted: the first, to determine the energy values and the second, the optimal supplementation level in the diet. The metabolism trial was conducted using 20 Leghorn cockerels divided into two treatments with five replicates of two birds each. The experiment lasted ten days, five ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The linear increase of NDFI is a consequence of higher neutral detergent fiber (NDF) levels in diets with BMF. Despite the BMF having a significant starch content [19], after mesocarp extraction, the flour may contain small amounts of epicarp and endocarp, resulting in a BMF with a greater fiber content and low starch content [7,20], which is likely for the BMF used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The linear increase of NDFI is a consequence of higher neutral detergent fiber (NDF) levels in diets with BMF. Despite the BMF having a significant starch content [19], after mesocarp extraction, the flour may contain small amounts of epicarp and endocarp, resulting in a BMF with a greater fiber content and low starch content [7,20], which is likely for the BMF used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…mesocarp flours subjected to drying in oven and solar dryer of 'babassu' flour can be influenced by the collection period, type of soil, maturity of the fruits, species and also type of mesocarp processing, handcrafted or industrial. The contents of total protein and crude fiber were higher in the studies that used 'babassu' flour as one of the components for animal feed, such as those conducted by Silva et al (2012), who found 14.49% of protein used in bovine diet, and Carneiro et al (2013), who found 3.29 and 2.66% of protein and fiber, respectively, used in the formulation of poultry feed.…”
Section: Resultsmentioning
confidence: 93%
“…The high standard of products and by-products obtained from babassu has been known for some decades, through laboratory experiments, considering each fraction of the coconut destined for some products such as, for example: epicarp (destined for charcoal with small granulometry, or alcohol , by hydrolysis of the cellulose it contains); mesocarp (produces starch, alcohol similar to that of cereals and the whole range of products derived from starch, which in turn has antiinflammatory and analgesic properties); endocarp (generates charcoal higher than some mineral coals, due to its high fixed carbon content and calorific value) and almond (intended for the production of industrial or edible oil) (Albiero et al, 2011;Carneiro et al, 2013;Chaves, 2006;de Menezes Pavlak et al, 2007;Porro, 2019;Santos, 2008;Soler et al, 2007;Sudre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%